(3EfHGA GdgUQ aj CHfGA GdYUQs - (3Ydj Hf OGhO Hf EHQGgje, fhQ GdOjf GdLhGgQj, GdeYQha HGHf GdUjQaj, hjbGd dg GHf OGhO,J (B900 (3g` s
(3ChdgG (B:s
(3SfI SJ hSHYjf KeGfi eGjI CgdJ gPg GdSJI hGdNdjaI GdeSJfLO HGddg CJi GdeXaQ jhSa GdYHGS OGe TQag hdjS dg ai GdNdGaI s
(3BNQgG (B:s
(3hdSJ eMJGL Gdjc hdGJXde CMOkG hGfeG JZQi HQOi hcf Ydi jbXI GPG CQOfG GQSGdc dge cd s
(3GdehLhO efg LRA jHOC ef Chd SfI (B873 (3Edi BNQ SfI (B877 (3eUhQ Yf fSNI HGQjSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B89s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B43 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B35 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs